KESEIMBANGAN HAK DAN KEWAJIBAN PARA PIHAK PADA TAHAP PRA-KONTRAKTUAL INFORMED CONSENT DI RUMAH SAKIT ZAINAB PEKANBARU - Ruziqna, Ananda; Firdaus, Firdaus; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The balance of the parties at the pre-contractual stage of informed consent at ZainabPekanbaru Hospital is interesting to study in depth. This is because there are still manyincidents where the patient and the hospital have not maximized the implementation ofthe pre-contractual stage even though informed consent has been carried out. Thepurpose of this study is, First, to find out how the balance of the parties is applied in thepre-contractual Informed Consent stage at Zainab Hospital Pekanbaru. Second, find outwhat conditions lead to non-fulfillment of the balance between the parties in the InformedConsent pre-contractual stage at Zainab Pekanbaru Hospital.This research uses the type of empirical legal research or sociological legal research.The sample in this study was Doctor, Nurse, and Patient of the Zainab Mother and ChildHospital, Pekanbaru City. The analytical tool in this study is a qualitative method. Thisstudy found that there were things that were less than optimal in reality on the ground,so it was necessary to anticipate them with maximum effort.This study concludes that, First, the application of the principle of balance of the partiesin the pre-contractual informed consent stage at Zainab Pekanbaru Hospital in fact, notreached balance. The hospital has tried its best to implement the principle of balance asbest as possible, but there are some patients who have problems implementing theprinciple of balance. Second, the situation that caused the principle of balance betweenthe parties to not be fulfilled in the pre-contractual stage of informed consent at ZainabHospital in Pekanbaru was caused by both parties. First, the circumstances that causethe patient's principle of balance to not be fulfilled consist of three causes, the first is thepatient's lack of knowledge of his rights and obligations. This is divided into 3 causes,namely the patient's level of education and experience, lack of information and socialculture and economics. Second, the patient does not provide honest and completeinformation about the disease he is suffering from. Third, the patient does not understandthe doctor's explanation, this is caused by 3 things, namely, the influence of age, theinfluence of education, the influence of work and at the pre-contractual stage, informedconsent was not explained. Second, the situation that causes the doctor's principle ofbalance to not be fulfilled, in the patient-doctor relationship, communication is active-passive. Doctors are active and patients are passive and only answer when asked or actafter being ordered by the doctor. The communication conveyed is also not clear, becausepatients lack medical terminology, and doctors do not provide opportunities for patientsto ask further questions about their medical condition.Keywords: Informed Consent – Balance – Pre Contractual